Briefing: A systemic framework for infrastructure need assessment. Issue 2 (December 2018) - Dolan, Tom
Abstract : In the absence of a clearly articulated, shared, collaboratively developed and mutually understood strategic vision of the desired outcomes that infrastructure is expected to enable (purpose), it is not possible to fully evaluate system performance gaps or assess infrastructure need. This is significant for any country, region, city, town or community aiming to cost-effectively improve the performance and resilience of its infrastructure systems. A systemic, collaborative, transparent, structured and flexible framework for infrastructure need assessment and decision-making is proposed. The proposed framework is systemic; is built on a set of strategic need assessment principles; explicitly aligns need assessment with the desired outcomes that infrastructure systems are expected to enable; prioritises underlying systemic priorities such as resilience; assesses infrastructure system performance and diagnoses infrastructure need from four perspectives; requires outcomes and needs to be neutrally framed; and prescribes transparent evaluation of options against clearly defined systemic and outcome-aligned selection criteria.